Analysis of the Influence of Abnormal Accrual, Internal Control System, and Audit Findings on the Quality of Government Financial Reports : (Study on District/City Governments in Indonesia) - Chyntia Dwi Putri; Rindu Rika Gamayuni; Fajar Gustiawaty Dewi; Kamadie Sumanda Syafis (International Journal of Economics and Management Sciences, 2024)
This study aims to exmine the influence of abnormal accrual, internal control system, and audit findings on the quality of financial reports of district/city goverments in Indonesia. The sampel that used in this study was local goverments in Indonesia at the district/city level in 2020-2022, with the sampel amounted to 1,518 sampels. The sampel selection is using purposive sampling technique and proceed using multinomial logistic regression analysis. The result of this study indicate that abnormal accrual do not affect the quality of local government financial reports. Then internal control system has a positive effect on the quality of local government financial reports. And audit finding has a negative effect on the quality of local government financial reports.